Traditional Knowledge and Use Value of Bamboo in Southeastern Benin: Implications for sustainable management - Honfo, Hermann; Tovissodé, Frédéric Chenangnon; Gnanglè, Césaire; Mensah, Sylvanus; Salako, Valère Kolawolé; Assogbadjo, Achille Ephrem; Agbangla, Clément; Glèlè Kakaï, Romain (Ethnobotany Research and Applications, 2015)
Traditional knowledge (TK), use, and economical values of three bamboo species—Oxytenanthera abyssinica (A.Rich.) Munro, Bambusa vulgaris Schrad. ex J.C.Wendl., and Dendrocalamus asper (Schult. & Schult. f.) Backer ex K.Heyne—were assessed in southeastern Benin. Individual interviews were used in 90 randomly selected villages, which cut across 10 socio-cultural groups. We tested and found evidence to support the hypotheses that (1) age, gender, and socio-cultural groups are predictors of TK and plant ethnobotanical use value and (2) bigger bamboo species are more expensive on the market. Bamboo was used for 44 purposes, but the common food use of bamboo shoots was not reported. Men and older people had more knowledge and valued bamboo more than women and younger people, respectively, indicating that they are key stakeholders for conservation actions. The culm was the most harvested part of bamboo, and its selling price was location- and size-dependent. The implications of these results are discussed with respect to conservation and management strategies for bamboo.